Comparative study on the role of PAM and PANA on the property of fresh cement paste. (October 2022) - Gu, Linan; Liu, Tiejun; Wu, Kai; Yang, Zhenghong; Wen, Zhaoyin; Zhang, Zhenlei; De Schutter, Geert; Li, Haoxin
Abstract: Both polyacrylamide (PAM) and sodium polyacrylate (PANA) are polypropylene based polymer, however it is still uncertain whether there are some differences between their roles on the property of fresh cement paste. Thus this work aimed to compare the property of fresh cement pastes with them, such as shear viscosity, fluidity, bleeding and water evaporation loss ratio. Meanwhile, the ultraviolet visible spectra, infrared spectroscopy and thermogravimetry were carried out to explore the mechanisms that are responsible for these differences. The experimental results indicate that as compared with PANA, PAM increases the shear viscosity and reduces the fluidity of cement paste more significantly. However, PANA more significantly reduces bleeding and water evaporation loss ratio. These differences are in conjunction with their different behaviors in the fresh cement paste, such as promotion in the cement hydration at early age and reaction with cement hydration product.